Automatic Alignment of Cranial CT Examinations to the Anterior Commissure/Posterior Commissure (ACPC) Reference Plane for Reliable Interpretation and Quality Assurance - Rubbert, Christian; Turowski, Bernd; Caspers, Julian (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Alignment of cranial CT scans (cCTs) to a common reference plane simplifies anatomical-landmark-based orientation and eases follow-up assessment of intracranial findings. We developed and open sourced a fully automated system, which aligns cCTs to the Anterior Commissure/Posterior Commissure (ACPC) line and exports the results to the PACS. FMRIB’s Linear Image Registration Tool (FLIRT) with an ACPC-aligned atlas is used in the alignment step. Five mm mean slabs are generated with the top non-air slice as the starting point. For evaluation, 301 trauma cCTs from the CQ500 dataset were processed. In visual comparison with the respective ACPC-aligned atlas, all were successfully aligned. Image quality (IQ) and ease of identification of the central sulcus (CS) were rated on a Likert scale (5 = excellent IQ/immediate CS identification). The median IQ was 4 (range: 2–4) in the original series and 5 (range: 4–5) in the ACPC-aligned series (p < 0.0001). The CS was more easily identified after fatbACPC (original scans: 4 (range: 2–5); ACPC-aligned: 5 (range: 4–5); p < 0.0001). The mean rotation to achieve alignment was |X| = 6.4 ± 5.2° ([–X,+X] = –26.8°–24.2°), |Y| = 2.1 ± 1.7° ([-Y,+Y] = –8.7°–9.8°), and |Z| = 3.1 ± 2.4° ([–Z,+Z] = –14.3°–12.5°). The developed system can robustly and automatically align cCTs to the ACPC line. Degrees of deviation from the ideal alignment could be used for quality assurance.Key Points:Citation Format
Keywords: multidetector computed tomography; neuroimaging; software; rotation; follow-up studies